2022
DOI: 10.1371/journal.pone.0261062
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-mediated Bag-1 knockout increased mesenchymal characteristics of MCF-7 cells via Akt hyperactivation-mediated actin cytoskeleton remodeling

Abstract: Bag-1 protein is a crucial target in cancer to increase the survival and proliferation of cells. The Bag-1 expression is significantly upregulated in primary and metastatic cancer patients compared to normal breast tissue. Overexpression of Bag-1 decreases the efficiency of conventional chemotherapeutic drugs, whereas Bag-1 silencing enhances the apoptotic efficiency of therapeutics, mostly in hormone-positive breast cancer subtypes. In this study, we generated stable Bag-1 knockout (KO) MCF-7 breast cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…S1 ). Besides, increased ROS generation has been reported following BAG1 knockout in MCF-7 cells ( 34 ). We therefore measured ROS production in MCF-7 and T47D cells after X15695 treatment using the fluorescent probe H2DCF-DA and showed a significant dose-dependent ROS production in MCF-7 but not in T47D cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S1 ). Besides, increased ROS generation has been reported following BAG1 knockout in MCF-7 cells ( 34 ). We therefore measured ROS production in MCF-7 and T47D cells after X15695 treatment using the fluorescent probe H2DCF-DA and showed a significant dose-dependent ROS production in MCF-7 but not in T47D cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One potential limitation of these studies, specific to our LNCaP95 CRISPR clones, is the challenges of a heterogenous cell population giving rise to biological differences independent of the genomic manipulation performed (59). Interestingly, studies in breast cancer cell line models have demonstrated differential response in growth to BAG-1 knockdown and it maybe that the biological background is important for sensitivity to BAG-1 abrogation which will be important to understand in the context of prostate cancer (58,60). This finding is important as drugs targeting the BAG domain would presumably impact all three isoforms, and not resemble the impact of BAG-1L specific knockouts or mutations previously described (14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%